Assessing the fourth industrial revolution: from a human resource management perspective - Elnur, Orujov (Dunakavics, 2024)
This study investigates the impact of increasing digitization, specifically Industry 4.0, on the labor market from the perspective of human resource specialists in the cosmetics industry in Baku and Sumgait. Using a mixed-methods approach that includes both synchronous (phone, Skype) and asynchronous (email) communication, data were gathered from 20 HR managers. The study focuses on HR professionals' views on digital transformation's effects on recruitment, wage differentiation, and workforce training. Findings suggest a growing need for advanced technological skills, highlighting the gap between current employee capabilities and those required for Industry 4.0. The study also underscores the importance of proactive training and adaptation strategies to navigate the digital transition, emphasizing a coordinated approach involving government, employers, and workers. As organizations increasingly adopt Industry 4.0 technologies, HR specialists anticipate challenges such as a shortage of skilled labor, potential wage disparities, and increased competition for tech-savvy employees. The findings call for an emphasis on quality and adaptability in workforce development to sustain employability in a rapidly evolving digital landscape.